Analisis Pengaruh Perceived Risk Terhadap Online Purchase Intention Pada Facebook Marketplace Masyarakat Batam Pendekatan Multi-Method - Hendi Sama; Henly . (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2023)
There are many risks that the general public needs to be aware of when purchasing on the internet. The purpose of this study is to comprehend some significant perceived risk implications for mass online purchasing on the Facebook marketplace. Population that was used in this study was the population of Batam City. The methodology of this study uses both quantitative and qualitative. The gathering of the research is carried out via online questionnaire and interviews. Following the collection of data, a multiple linear regression was used for analysis. The results of this study indicate that there may be a connection between indicators of finance risk and psychological risk and the general public's willingness to buy. This was done using a quantitative method that indicated the existence of any evidence linking product risk to consumer purchasing behavior. This is supported by a qualitative study that shows how people's purchasing intentions are influenced by product risk concerns. In order to boost Batam City residents' intentions to make online purchases, this study makes recommendations on Facebook for reducing the impact of finance risk factors, psychological risk factors, and product risk factors.Top of Form